2016
DOI: 10.1158/0008-5472.can-16-0266
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Plasticity as a Determinant of Tumor Growth and Metastasis

Abstract: Cancer cells must adapt their metabolism to meet the energetic and biosynthetic demands that accompany rapid growth of the primary tumor and colonization of distinct metastatic sites. Different stages of the metastatic cascade can also present distinct metabolic challenges to disseminating cancer cells. However, little is known regarding how changes in cellular metabolism, both within the cancer cell and the metastatic microenvironment, alter the ability of tumor cells to colonize and grow in distinct secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
181
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(190 citation statements)
references
References 95 publications
(98 reference statements)
7
181
0
2
Order By: Relevance
“…Here, we propose that during their evolution, tumor cells acquire a metabolic signature adapted for survival at particular metastatic sites, which dictates where they are able to form distal colonies. This hypothesis is consistent with the growing body of evidence showing that the more metabolically flexible the primary tumor cells are, the more likely they are to survive the metastatic process and thrive in distant organs (Lehuede et al, 2016). …”
supporting
confidence: 88%
“…Here, we propose that during their evolution, tumor cells acquire a metabolic signature adapted for survival at particular metastatic sites, which dictates where they are able to form distal colonies. This hypothesis is consistent with the growing body of evidence showing that the more metabolically flexible the primary tumor cells are, the more likely they are to survive the metastatic process and thrive in distant organs (Lehuede et al, 2016). …”
supporting
confidence: 88%
“…In addition to serving as a source of energy and metabolites for proliferating cancer cells 11,36,41,42 , mitochondria have been described as essential during migration and metastasis in breast cancer cells 15,16 . During migration and metastasis, cancer cells must adhere to the extracellular matrix (ECM) 43 .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, invasive metastatic breast cancer cells specifically favor mitochondrial respiration, to increase ATP levels, through a mechanism that involves overexpression of PGC-1α and increase mitochondrial biogenesis 14 . In fact, it has been shown that OXPHOS activity increases concomitantly with the metastatic potential in primary breast cancer 15,16 . Therefore, mitochondrial metabolism represents an attractive target for anti-metastatic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells must display a high metabolic plasticity to generate the energy and to meet the biosynthetic demand required to support their proliferation and dissemination in a poorly oxygenated and nutrient-deprived microenvironment (59,60 Moreover, in contrast to normal cells, cancer cells can simultaneously synthesize and utilize FAs through fatty acid oxidation (FAO) (67). The key role of FAO in cancer cell metabolism has recently emerged (68,69).…”
Section: Metabolic Remodeling In Tumor Cells Emerging Role Of Fa Metmentioning
confidence: 99%